The African Languages Research Institute: A Milestone in the Development of the Zimbabwean Languages - Chabata, Emmanuel (Lexikos, 2007)
Abstract: This article is an assessment of the work the African Languages Research Institute (ALRI) has done towards developing the indigenous languages of Zimbabwe. It looks at what the research team at ALRI has achieved, first in initiating serious research on the Zimbabwean languages and the progress it has made towards achieving its goal, developing and raising the status of these languages. It also considers what ALRI has planned for the future of the different categories or levels into which the various Zimbabwean languages have been classified. Part of the assessment focuses on measures ALRI has put in place to ensure the initiated research programme is sustainable and will continue in future. The article furthermore discusses the importance of the research work being done at ALRI, especially with regard to language development as a means towards self-realisation and actualisation, national advancement and the sustenance of the languages involved. ALRI's agenda is also analysed to see how well it agrees with popular thinking in Zimbabwe concerning the development and promotion of all of the indigenous languages.Keywords: ALRI, CAPACITY BUILDING, INSTITUTIONALISATION, LANGUAGE HAR-MONISATION, LANGUAGE STANDARDISATION, MONOLINGUAL LEXICOGRAPHY, ZIM-BABWEAN LANGUAGESOpsomming: Die African Languages Research Institute: 'n Mylpaal in die ont-wikkeling van die Zimbabwiese tale. Hierdie artikel is 'n evaluering van die werk wat die African Languages Research Institute (ALRI) gedoen het in die ontwikkeling van die inheemse tale van Zimbabwe. Dit kyk na wat die navorsingspan bereik het, eerstens deur ernstige navorsing oor die Zimbabwiese tale te onderneem en die vordering wat gemaak is met die bereiking van sy doel, die ontwikkeling en die statusverhoging van hierdie tale. Dit beskou ook wat ALRI beplan het vir die toekoms van die verskillende kategorieë of vlakke waarin die onderskeie Zimbabwiese tale geklassifiseer is. 'n Deel van die evaluering fokus op maatreëls wat ALRI in plek gestel het om te verseker dat die onderneemde navorsingsprogram volhoubaar is en in die toekoms sal voortgaan. Verder bespreek die artikel die belangrikheid van die navorsingswerk wat by ALRI gedoen word, veral met betrekking tot taalontwikkeling as 'n manier tot selfverwesenliking en -aktualisering, nasionale vooruitgang en die onderhoubaarheid van die betrokke tale. ALRI se agenda word ook ontleed om te sien hoe goed dit ooreenstem met die algemene denke in Zimbabwe betreffende die ontwikkeling en bevordering van al die inheemse tale.Sleutelwoorde: ALRI, VERMOÃ‹NSBOU, INSTITUSIONALISERING, TAALHARMONI-ERING, TAALSTANDAARDISERING, EENTALIGE LEKSIKOGRAFIE, ZIMBABWIESE TALE